Developing a Research Agenda for Adult Palliative Care: A Modified Delphi Study - Sullivan, R.; Ugalde, A.; Sinclair, C.; Breen, Lauren (MARY ANN LIEBERT, INC, 2019)
Background: Little is known about research priorities in adult palliative care. Identifying research priorities for adult palliative care will help in increasing research quality and translation. Objective: The aim was to identify the views of health professionals' research priorities in adult palliative care that lead to development of a palliative care research agenda in Australia. Design: A modified three-round Delphi survey. Setting/Subjects: Palliative care researchers and clinicians in Australia were invited to participate. Results: A total of 25 panelists completed round 1, 14 completed round 2, and 13 completed round 3. Round 1 resulted in 90 research priorities in 13 categories. Round 2 showed consensus agreement on 19/90 research priorities. Round 3 resulted in the top 10 research priorities of the 19 achieving consensus in round 2. Panelists agreed that research is needed on the transition to palliative care; improving communication about prognosis; increasing access to palliative care for indigenous communities, people who wish to remain at home, and people in aged care; addressing family caregivers' needs; promoting patients' and families' decision making; improving cross-cultural aspects of palliative care; determining the effects of assisted dying legislation; and improving bereavement care in rural, remote, and Aboriginal populations. Conclusions: The expert panelists identified the top 10 research priorities for adult palliative care. These identified research priorities are the most urgent topics requiring attention to increase the quality of life of patients requiring palliative care and their family members.